Evaluation of prognostic risk factors at diagnosis and treatment outcomes in adult patients with early-stage hodgkin lymphoma in Cape Town, South Africa - Dawood, Shakira (Department of Medicine, 2025)
The National Comprehensive Cancer Network (NCCN) Guidelines are a recognized standard for prognostic staging in Hodgkin Lymphoma (HL). We aimed to determine if the NCCN staging system and its individual risk factors correlated with patient treatment outcomes in early-stage adult classical HL (cHL) patients. This retrospective study included 70 patients diagnosed with and treated for early-stage (stage I and II) cHL from 2010 to 2022, at Groote Schuur Hospital Radiation Oncology and Clinical Haematology Units. NCCN unfavourable risk factors assessed were mediastinal mass ratio, presence of bulky disease, B-symptoms, number of nodal regions involved and erythrocyte sedimentation rate. Patients were divided into early-stage favourable (no unfavourable factors) and early-stage unfavourable (any unfavourable factors). Kaplan-Meier curves and log-rank tests were used to compare treatment outcomes between groups. The median age at diagnosis was 35 years and 50% of the patients were male. Most patients had stage II disease (86%) and were classified as unfavourable (76%). During the study period, 6 patients died (9%) all of whom had stage II unfavourable disease. The 5-year overall survival for the favorable and unfavourable groups was similar (94% vs. 90%, P=0.599). Progression free survival at 5 years was also similar (83% vs. 88%, P=0.984). This study demonstrates excellent 5-year survival outcomes in early-stage cHL patients. These findings are comparable with those in higher income countries and were not affected by HIV status or unfavourable risk factors. This highlights the importance of early diagnosis and treatment while patients still have early-stage disease